Rencontres radicales : pour des dialogues féministes décoloniaux - Altamimi, Manal; Dor, Tal; Guénif Souilamas, Nacira (Cambourakis, 2018)
Comment tenter de trans/former la conscience de personnes engagées dans des situations de conflit, des tensions sociales et raciales et en quête de changements politiques significatifs ? Trois types de textes se font ici écho : six auteur·e·s analysent les « rencontres radicales » organisées entre Palestinien·ne·s et Israélien·ne·s ; bell hooks écrit sur l’éducation à/par l’émancipation dans le contexte des discriminations raciales aux États-Unis ; enfin, trois participant·e·s à des groupes de rencontre en Kanaky/Nouvelle-Calédonie nous proposent un troisième point d’ancrage en cette année de référendum d’autodétermination. Un ouvrage collectif qui vise à donner voix ensemble aux militant·e·s et aux théories, engageant un dialogue qui offre un répertoire d’actions et de réflexions puissant et décapant au confluent du féminisme, de l’analyse de la colonialité et d’une radicalité revendiquée. Essais de bell hooks, Rabah Halabi, Michal Zak, Nava Sonnenschein, Ramzi Suleiman, Ahmad Hijazi, Tal Dor, Angélina Perrochaud, Pascal Hébert, Pierre Wélépa et Nassira Hedjerassi.
Postface de Nassira Hedjerassi
Keywords: afrique; amériques; approches et analyses; asie; cours; fem3100; féminisme décolonial; histoire et politique; israël; militance; nouvelle calédonie; océanie; palestine; premier cycle; régions géographiques; thématiques; états-unis

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative